2015
DOI: 10.1021/acs.jced.5b00046
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Normal Boiling Temperatures, Critical Properties, and Acentric Factors of Deep Eutectic Solvents

Abstract: Deep eutectic solvents (DESs) are novel solvents that have shown the ability to capture carbon dioxide from flue gases. Thermodynamic modeling is needed to validate the experimental vapor–liquid equilibria (VLE) of the CO2–DES systems. To establish thermodynamic models of these solvents, their critical properties must be estimated. In the present study, a combination of the modified Lydersen–Joback–Reid (LJR) method and the Lee–Kesler mixing rules has been applied to estimate the critical properties of 39 diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 49 publications
2
45
0
6
Order By: Relevance
“…For this we require the molecular weight, density, boiling point, viscosity, COSMO cavity volume term, and sigma profiles. For boiling point, the Lydersen−Joback−Reid method is used to calculate the normal boiling point of DES as given below Tnormalb=198.2+niΔTbMi…”
Section: Resultsmentioning
confidence: 99%
“…For this we require the molecular weight, density, boiling point, viscosity, COSMO cavity volume term, and sigma profiles. For boiling point, the Lydersen−Joback−Reid method is used to calculate the normal boiling point of DES as given below Tnormalb=198.2+niΔTbMi…”
Section: Resultsmentioning
confidence: 99%
“…erefore, the critical temperatures T c , which are on the average about 4/3(T b /K) [1], are not the quantities that are relevant to their applications but have found use for the estimation of other properties that have not been measured as functions of the temperature [1,4]. Still, the critical temperatures are physical properties that ought to be known; hence, the present estimates for two dozens of deep eutectic solvents of which only eight had their T c estimated previously make sense.…”
Section: Discussionmentioning
confidence: 99%
“…ese mixtures are liquid at room temperature and freeze at a temperature considerably below the freezing points of the components, and hence, they are eutectics. Mirza et al [1] reported a group additivity method for the estimation of the critical temperatures T c (also the boiling points and densities) of deep eutectic solvents. An alternative path for the estimation of the critical temperatures is described here for deep eutectic solvents that for most of them no previous estimates were reported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations